2003
DOI: 10.1046/j.1095-8312.2003.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics in the quantification of character state identity for the assessment of primary homology: an analysis of character variation of the genus Artibeus (Chiroptera: Phyllostomidae)

Abstract: The recognition of transformed homologues entails an evaluation of similarity of features among taxa and then an assessment of homology by character congruence. We approached the similarity test of character state identity with morphometric analyses of character variation to judge whether all variants from a taxonomic sample belong to the same phylogenetic state (taxic homology) or whether some variants are sufficiently different to recognize them as different states (transformational homology). This method se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 61 publications
4
19
0
10
Order By: Relevance
“…Combined studies of morphometric and molecular data to answer phylogenetic hypothesis has been found to be highly consistent and in agreement (Caumul & Polly, 2005;Clouse et al, 2009;Giribet et al, 2012), indicating that the morphometric data contain significant phylogenetic information. Moreover, it has been found that phylogenetic analyses based solely on morphometric data can produce strong hypotheses (Guerrero et al, 2003;González-José et al, 2008;de Bivor et al, 2010;Soto-Vivas et al, 2011). The results show a strong agreement with previous molecular results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Combined studies of morphometric and molecular data to answer phylogenetic hypothesis has been found to be highly consistent and in agreement (Caumul & Polly, 2005;Clouse et al, 2009;Giribet et al, 2012), indicating that the morphometric data contain significant phylogenetic information. Moreover, it has been found that phylogenetic analyses based solely on morphometric data can produce strong hypotheses (Guerrero et al, 2003;González-José et al, 2008;de Bivor et al, 2010;Soto-Vivas et al, 2011). The results show a strong agreement with previous molecular results.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the use of morphometrics in systematic contexts has undergone a clear revival (Humphries, 2002) through the development of new methodologies that allow a more efficient and elegant use of shape information, such as the direct use of x, >; (and 3D) coordinates (Catalano et al, 2010). Phylogenetic analyses based on geometric morphometrics have shown that morphometric data contain considerable historic signals (Felsenstein, 1988(Felsenstein, , 2002Guerrero et al, 2003;Caumul & Polly, 2005;Goloboff et al, 2006;González-José et al, 2008;de Bivort et al, 2010;Soto-Vivas et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Utiliza-se aqui no lugar de A. jamaicensis Leach, 1821. Embora o táxon tenha uma posição sistemática um pouco controversa, sendo considerada por alguns autores como subespécie ou sinônimo de A. jamaicensis, seguimos as propostas de GUERRERO et al (2003), LIM et al (2004) e LARSEN et al (2007, onde A. planirostris é considerada uma espécie plena, o que é também seguido por diversos autores (BARQUEZ et al, 1991(BARQUEZ et al, , 1999SIMMONS, 2005;BARQUEZ, 2006;ZORTÉA, 2007).…”
Section: Resultsunclassified
“…Bats were identified using field keys (Medellín et al 1997). Because no conclusive evidence exists to the contrary (Guerrero et al 2003;Redondo et al 2008), we recognized A. intermedius as a valid species, following the most recent nomenclature for the terrestrial mammals of Mexico (Ramírez-Pulido et al 2005). Abundance was quantified as the total number of individuals captured per forest fragment or coffee plantation.…”
Section: Data Collectionmentioning
confidence: 99%